Effects of physical exercise on articular range of motion of the lower limb in the Parkinson's disease individuals - Fabio Augusto Barbieri; Rosangela Alice Batistela; Natália Madalena Rinaldi; Claudia Teixeira-Arroyo; Florindo Stella; Lilian Teresa Bucken Gobbi (Universidade de São Paulo, 2014)
The aim of this study was to investigate the effect of eight months of a multimodal program of physical exercise on articular range of motion of the lower limb of patients with Parkinson disease (PD), considering gender and disease stage. Seventeen individuals with PD participated in this study. Participants were assessed before of multimodal program of the physical exercise and after four and eight months of physical exercise. In these periods were evaluated the clinical aspects and articular range of motion of the lower limb. For statistical analysis, patients were distributed according to gender and disease stage. A MANOVA considering exercise, gender and stage of disease, with repeated measures for the first factor, was performed. The clinical results showed regression of disease progression, indicating cognitive decline for women. The articular range of motion improved after four and eight months of physical exercise, especially for the hip and ankle, independent of gender and stage of PD. It was concluded that the multimodal exercise program of the eight months was effective in improving articular range of motion in patients with PD. The benefits of exercise for this physical capacity were independent of gender and severity of PD.